THE SIGNIFICANCE OF THE SEDEKAH LAUT TRADITION IN FOSTERING SOLIDARITY AND EDUCATIONAL VALUES AMONG THE COMMUNITY OF TASIK AGUNG VILLAGE, REMBANG - theresia indah septalia; Muhammad Iqbal Birsyada (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to explore the significance of the “sedekah laut” tradition in fostering social solidarity and educational values among the community of Tasik Agung Village, Rembang. The study employs a qualitative approach using observation, interviews, and documentation. The research informants consist of traditional leaders, fishermen, and local residents. Data analysis was conducted through the stages of data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that the sea offering tradition is not only a cultural heritage of coastal communities but also serves to strengthen social bonds through mutual aid and cooperation among residents. This tradition also instills values of responsibility, discipline, social concern, and an awareness of preserving local culture in the younger generation. Symbols within the tradition, such as offerings, communal prayers, and the ritual of casting objects into the sea, are interpreted as expressions of gratitude, hopes for safety, and respect for ancestral culture. Thus, the sea offering tradition serves as a means of cultural preservation as well as a medium for social education for the community of Tasik Agung Village, Rembang.